2017 IEEE 3rd International Forum on Research and Technologies for Society and Industry (RTSI) 2017
DOI: 10.1109/rtsi.2017.8065886
|View full text |Cite
|
Sign up to set email alerts
|

An assistive mobile system supporting blind and visual impaired people when are outdoor

Abstract: In this paper we present the TARSIUS system, based on mobile technology and aimed at enhancing visually-impaired and blind people's capabilities in visual scene understanding and geolocation while are outdoor. The system components are the TARSIUS app for mobile devices, a web server, and the Remote Assistance Center. Its interface is optimized for the perceptual characteristics of its users. Moreover, the TARSIUS navigation sub-system not only leverages the GPS system, but also Bluetooth LE/iBeacon tags place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The TARSIUS system [83] aimed at enhancing the capability of users in the visual scene understanding of the outdoor environments. The system components include the TARSIUS app for mobile devices, a web server, a remote assistance centre, and also the Bluetooth LE/iBeacon tags placed along the streets at points of interest.…”
Section: Smartphone-based Solutionsmentioning
confidence: 99%
“…The TARSIUS system [83] aimed at enhancing the capability of users in the visual scene understanding of the outdoor environments. The system components include the TARSIUS app for mobile devices, a web server, a remote assistance centre, and also the Bluetooth LE/iBeacon tags placed along the streets at points of interest.…”
Section: Smartphone-based Solutionsmentioning
confidence: 99%
“…Within the games, she could see the sharp contrasts but could not see any of the details that were camouflaged or too close in color to other aspects within the game. She compared the game experience to other experiences and technologies, such as mobile warning devices (Mataro et al, 2017) and VR devices that calibrate to vision impairment and help to see details that cannot be seen with only corrective lenses in glasses (See online advertisements for Jordy devices). Her experiences with physical O&M training over the years were insightful to assess the aspects of the gaming environments for possible implementation using educational technology for O&M training and practice; something that is being driven by economic factors.…”
Section: Resultsmentioning
confidence: 99%
“…The foremost reason behind the visual loss or impairment is mainly glaucoma (2%), unoperated cataract (33%) and uncorrected refractive errors: astigmatism or hyperopia, myopia (43%). Overall, 80% of the all the visual impairments can be prevented or cured [2]. WHO also reported that people with sensory disabilities affect 5.3% of the world population and 9.3% of the world population for audition and vision impairments respectively [3].…”
Section: Introductionmentioning
confidence: 99%